Plant migration : the dynamics of geographic patterning in seed plant species - Sauer, Jonathan D. (University of California Press, 1988)
Using cases of plant migration documented by both historical and fossil evidence, Jonathan D. Sauer provides a landmark assessment of what is presently known, and not merely assumed, about the process.